Evaluating the Success Rate of Dental Implants in Diabetic Patients: A Systematic Review of Clinical Outcomes and Risk Factors - Feddah, Khalil Mohammed Ahmed; Almashhoor, Ahmmed Osama Zaid; Sait, Fawaz Mohamed; Maroof, Ali Mohammed; Noorwali, Khalid Ahmed; Alothmani, Ayman Hammad; Halawani, Motazz Sami; Alkhateeb, Abdulhamid Mohammed; Albalbisi, Ayman Mohammed; AlSayyali, Mohammed Mohsen; Hilmi, Mohammad Amged H (Journal of Ecohumanism, 2024)
Diabetes mellitus is a chronic condition that poses significant challenges for dental health, particularly in the context of dental implants, where effective osseointegration and healing are crucial for success. Diabetic patients may experience delayed wound healing and increased susceptibility to infections, potentially impacting the success rate of dental implants. This systematic review aims to evaluate the success rates of dental implants in diabetic patients compared to non-diabetic individuals and to identify key clinical outcomes and risk factors influencing implant success. A comprehensive literature search will be conducted across major databases, including PubMed, Cochrane Library, and Embase, for studies published from 2016 onwards. Studies assessing implant success rates, complications, and relevant factors such as glycemic control and diabetes type will be included. Data will be extracted systematically, and quality assessment tools will be applied to evaluate the risk of bias. Findings from this review are expected to clarify the impact of diabetes on implant outcomes, provide evidence-based recommendations for managing diabetic patients undergoing implant procedures, and highlight areas for further research.